1998
DOI: 10.1093/nar/26.10.2313
|View full text |Cite
|
Sign up to set email alerts
|

oriGNAI3: A narrow zone of preferential replication initiation in mammalian cells identified by 2D gel and competitive PCR replicon mapping techniques

Abstract: The nature of mammalian origins of DNA replication remains controversial and this is primarily because two-dimensional gel replicon mapping techniques have identified broad zones of replication initiation whereas several other techniques, such as quantitative PCR, have disclosed more discrete sites of initiation at the same chromosomal loci. In this report we analyze the replication of an amplified genomic region encompassing the 3'-end of the GNAI3 gene, the entire GNAT2 gene and the intergenic region between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 43 publications
1
30
0
Order By: Relevance
“…The oriGNAI3 was identified in the intergenic region between the GNAI3 and GNAT2 genes and oriB in the AMPD2 3' segment (13,23). The p4.4 kb plasmid (Y08232.1) that contains the intergenic region GNAI3-GNAT2 and the p2.5 kb (X96547) plasmid that contains the 3' segment of the AMPD2 gene were purified by the CTAB method (24) and cleaved with restriction endonucleases according to the manufacturer's instructions.…”
Section: Restriction Fragmentsmentioning
confidence: 99%
“…The oriGNAI3 was identified in the intergenic region between the GNAI3 and GNAT2 genes and oriB in the AMPD2 3' segment (13,23). The p4.4 kb plasmid (Y08232.1) that contains the intergenic region GNAI3-GNAT2 and the p2.5 kb (X96547) plasmid that contains the 3' segment of the AMPD2 gene were purified by the CTAB method (24) and cleaved with restriction endonucleases according to the manufacturer's instructions.…”
Section: Restriction Fragmentsmentioning
confidence: 99%
“…Some examples of this phenomenon include DNA segments that form DNA puffs in Sciaridae and the chorionic gene-containing chromosome segment in Drosophila melanogaster (Claycomb and Orr-Weaver, 2005). Examples of DNA amplification induced in vitro in cultured mammalian cells include the dihydrofolate reductase gene amplification in ovarian cells (Dijkwell et al, 1991;Altman and Fanning, 2004) and the adenosine monophosphate deaminase 2 gene amplification in Chinese hamster lung cells (Toledo et al, 1998;Anglana et al, 2003;Courbet et al, 2008). Gene amplification has also been reported to occur during the course of tumorigenesis in distinct chromosomal regions (Myllykangas and Knuutila, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The nature of the information required for activation of replication origins in multicellular organisms, where multiple initiation sites of replication occur in cells with differential gene expression, has made it difficult to associate function to a specific replication origin sequence. Analyses of replication intermediates using alternative methods indicated that the replication origin lacked a nucleotide consensus sequence (Biamonti et al, 2003;DePamphilis, 1999;Toledo et al, 1998;Tower, 2004). The activity of the initiation site for replication in metazoans, which lacks a consensus sequence, can be influenced by chromatin structure and/or selected by epigenetic factors (Anglana et al, 2003;Balani et al, 2010;Courbet et al, 2008;Debatisse et al, 2004;Fiorini et al, 2006a;Gimenes et al, 2009;Stehle et al, 2003).…”
Section: Introductionmentioning
confidence: 99%